Synthesis and determination of the Sun Protection Factor of a cosmetic gel-cream based on norbixin - Garcia, Simey do Vale; Alves, Patrícia e Silva; Dias, Leandro de Sousa; Santos, Leandro Josuel da Costa; Lustosa, Sérgio Marcelo Coelho; Viana, Deuzuíta dos Santos Freitas; Viana, Vicente Galber Freitas (Seven Editora, 2023)
This work aimed to determine the Sun Protection Factor (SPF) of a cream-gel based on norbixin through spectrophotometry. Samples of gel-cream A and B were prepared at a concentration of 0.2 μL/mL and the absorbances were measured in the UVB region and the SPF was calculated using the equation used in the Mansur method. The absorption spectrum of each cream-gel was obtained using the origin program. Gel-creams A and B showed absorption in the UVA and UVB region and also in the long UVA region, therefore, they presented photoprotective characteristics. Regarding the Sun Protection Factor - SPF, both the cream-gel A and the cream-gel B were considered photoprotective by ANVISA. Norbixin increased the Sun Protection Factor - SPF and this potentiation was proportional to its concentration. Therefore, the use of norbixin in photoprotective products proved to be effective, favoring an increase in the photoprotection of the formulations. DOI:https://doi.org/10.56238/globalhealthprespesc-069